Micro-Incision Vitreoretinal Surgery in Cases of Idiopathic Macular Hole at a Tertiary Care Hospital - Rizwi, Syed Fawad; Khan, Muhanmmad Abdullah; Kamil, Zeeshan; Bokhari, Syeda Aisha; Murtaza, Faisal; Feroze, Lubna (Pakistan Journal of Ophthalmology, 2017)
Purpose: To assess the anatomical and visual results of micro incision vitreoretinal surgery (MIVS) in patients with idiopathic macular hole. Study Design: Quasi experimental study. Place and Duration of Study: LRBT Free Base Eye Hospital, Karachi from January 2014 to December 2014. Material and Methods: The study included 18 eyes of 18 patients with idiopathic macular hole, who underwent MIVS with dye assisted internal limiting membrane (ILM) peeling and 14% perfluoropropane (C3 F8) as internal tamponade. Outcome measures were post-operative visual acuity and anatomical closure. Post-operative follow-up was conducted up to 6 months after the surgery. Results: Eighteen patients were recruited for the study, out of which 11 (61%) were male and 07 (39%) were female. Age ranged from 45 – 70 years (mean age 60.8 ± 5.2 years). Visual improvement of up to 2 lines was seen in 11 (61%) of the patients, whereas, anatomical closure was achieved in 16 (88%) of the patients. Conclusion: Micro incision vitreoretinal surgery (MIVS) in patients with idiopathic macular hole resulted in high anatomical success and significant visual improvement. Keywords: Microincision vitreoretinal surgery, idiopathic macular hole, perfluoropropane.